Empowering Educators in Academic Writing: An International Community Engagement Initiative on Systematic Literature Reviews - Yulita Fairina Susanti; Cut Sjahrifa Zahirsjah; Samuel PD Anantadjaya (Institut IPMI, 2026)
This study evaluates an international community development initiative titled